Evaluation of nerve fiber layer and ganglion cell complex changes in patients with migraine using optical coherence tomography - Yasmin Walha; Mona Rekik; Khadija Sonda Moalla; Sonda Kammoun; Omar Ayadi; Chokri Mhiri; Mariem Dammak; Amira Trigui (eNeurologicalSci)
Purpose: To analyze changes in peripapillary retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC) thickness in migraine patients with and without aura compared to healthy controls and to identify factors influencing the occurrence of these anomalies. Methods: This is a cross-sectional case-control study including migraine patients and control subjects. All patients and controls underwent a complete ophthalmological examination, RNFL and GCC thickness measurements using a spectral domain-OCT device.The duration of migraine, the frequency and duration of migraine attacks, the migraine disability assessment (MIDAS) and migraine severity scale (MIGSEV) questionnaire scores were recorded. Results: One hundred and twenty eyes from 60 patients (60 eyes in the migraine without aura (MWoA) group and 60 eyes in the migraine with aura (MWA) group) were included. Control group included 30 age and gender matched healthy participants (60 eyes). OCT revealed that RNFL and GCC thickness were significantly reduced in the migraine without aura (MWoA) and in the migraine with aura (MWA) groups compared to the control group and in the migraine with aura (MWA) group compared to the migraine without aura (MWoA) group. Prolonged disease duration was associated to decreased GCC thickness. RNFL and GCC thickness were correlated to disease severity, attack frequency and duration. In the multivariate study, duration of migraine and attack frequency were the main determinant factors of nasal GCC thickness. Disease severity was the main determinant of RNFL and GCC thickness, with the exception of the nasal sector. Conclusion: Our study emphasize the significant impact of both types of migraine on retinal structures. OCT would serve as a valuable biomarker in migraine.